2014 Update on Interventional Cardiology - Hernández Hernández, Felipe; de la Torre Hernández, José M.; Rumoroso Cuevas, José R.; García del Blanco, Bruno; Martínez-Sellés, Manuel; Trillo Nouche, Ramiro (Revista española de cardiología (English ed.), 2015)
This article reviews the most relevant publications and studies in the field of interventional cardiology in 2014. In the area of coronary interventional procedures, integrated treatment of acute coronary syndrome continues to be the subject of numerous studies that evaluate different devices and pharmacological and mechanical strategies that can be used without increasing the risk of hemorrhage or the need for reintervention. Certain anatomical substrates continue to generate a considerable number of publications, both on the outcomes with different stents and on the use of specific techniques. Bioabsorbable drug-eluting stents are used in increasingly complex lesions with promising results. The development of interventional procedures for structural heart disease continues to advance, with new evidence on percutaneously placed aortic valve prostheses, the outcome of percutaneous mitral valve repair, and the safety and efficacy of left atrial appendage occlusion. Finally, renal denervation has generated one of the major debates of the year. Este artículo presenta una revisión de las publicaciones y los estudios más relevantes en el ámbito de la cardiología intervencionista en el año 2014. Dentro del intervencionismo coronario, el tratamiento integral del síndrome coronario agudo sigue siendo objeto de múltiples estudios que evalúan diferentes dispositivos y estrategias farmacológicas y mecánicas sin incrementar el riesgo de hemorragia ni la necesidad de reintervención. Algunos sustratos anatómicos particulares siguen generando un importante número de publicaciones, tanto por los resultados de diferentes stents como por el uso de técnicas específicas. Los stents farmacoactivos bioabsorbibles se emplean en lesiones cada vez más complejas con resultados prometedores. El intervencionismo cardiaco estructural avanza en su desarrollo: nuevas evidencias con las prótesis aórticas percutáneas, resultados de la reparación mitral percutánea o seguridad y eficacia de la oclusión de la orejuela izquierda. Finalmente, la denervación renal ha generado uno de los grandes debates del año.